(untitled) (Research, Society and Development, 2023)
The COVID-19 pandemic, declared by the World Health Organization (WHO) in 2020 as a global health emergency, has affected the mental health of nurses on the front line fighting the infection. A significant number of health professionals were found to have become ill or died as a result of the disease. This led to psychological challenges, such as fear of contamination, physical and emotional exhaustion and difficulties in carrying out the profession. This article addresses the complexity and challenges faced by nurses in their daily professional lives, highlighting adversities related to mental health. Based on studies, it is emphasized that nurses play leadership roles in the healthcare team, being essential for providing care to patients. The pandemic has introduced a series of unique challenges for these professionals. Thus, the need for effective approaches to protect the mental health of nurses, offering psychological support and adequate training, is evident. The objectives of this research were to carry out a comprehensive and systematic integrative review to assess the impacts of the COVID-19 pandemic on the mental health of nurses and to understand in depth the psychological implications of the pandemic on these professionals. This is an integrative review of the literature. This type of study is a method that adapts the synthesis of knowledge and the annexation of the applicability of results from significant studies in practice. The sample included 9 articles, considering several studies that address the topic, it is clear that the health crisis had significant repercussions in this crucial sector.